A Storytelling Approach on Vocabulary, Reading, and Letter Sound Fluency of Struggling First Graders With German as Second Language With and Without Behavioral Problems - Barwasser, Anne; Bracht, Janine; Grünke, Matthias (Frontiers in Psychology, 2021)
The number of students learning German as a second language (L2) is steadily increasing. Unfortunately, studies reveal that less-proficient school performance affects a larger proportion of these students and additional behavioral problems can create even greater learning barriers. In order to master a language, the focus is not only on vocabulary, but also on reading, and studies show that multi-component intervention in reading and L2 acquisition is particularly promising. Therefore, this multiple baseline study focuses on a multi-component storytelling intervention on vocabulary, reading, and letter sound fluency of low-achieving first graders with German as L2 with and without behavioral problems (N = 7). The intervention was implemented 3 times a week over a 6-week period. Results show significant large to very large effects on vocabulary and moderate to large effects on letter sound fluency and reading, providing indication for the positive impact of storytelling on multiple aspects simultaneously for the focused sample.